Voluntary HIV counseling and testing during prenatal care in Brazil - Goldani, Marcelo Zubaran (2003)
OBJECTIVE: Voluntary HIV counseling and testing are provided to all Brazilian pregnant women with the purpose of reducing mother-to-child HIV transmission. The purpose of the study was to assess characteristics of HIV testing and identify factors associated with HIV counseling and testing. METHODS: A cross-sectional study was carried out comprising 1,658 mothers living in Porto Alegre, Brazil. Biological, reproductive and social variables were obtained from mothers by means of a standardized questionnaire. Being counseling about HIV testing was the dependent variable. Confidence intervals, chi-square test and hierarchical logistic model were used to determine the association between counseling and maternal variables. RESULTS: Of 1,658 mothers interviewed, 1,603 or 96.7% (95% CI: 95.7-97.5) underwent HIV testing, and 51 or 3.1% (95% CI: 2.3-4.0) were not tested. Four (0.2%) refused to undergo testing after counseling. Of 51 women not tested in this study, 30 had undergone the testing previously. Of 1,603 women tested, 630 or 39.3% (95% CI: 36.9-41.7) received counseling, 947 or 59.2% (95% CI: 56.6-61.5) did not, and 26 (1.6%) did not inform. Low income, lack of prenatal care, late beginning of prenatal care, use of rapid testing, and receiving prenatal in the public sector were variables independently associated with a lower probability of getting counseling about HIV testing. CONCLUSIONS: The study findings confirmed the high rate of prenatal HIV testing in Porto Alegre. However, women coming from less privileged social groups were less likely to receive information and benefit from counseling.